Deflocculation of kaolin suspensions - The effect of various electrolytes - Penkavova, V. (2015)
Viscosity reduction of aqueous kaolin suspensions by conventional additives (deflocculation) is studied, using standard viscosity measurements. Apparent viscosity at 100 s-1, and flow behavior index n give complex information about changes of viscosity and flow character of deflocculated suspensions. Several widely used deflocculants - electrolytes and polyelectrolytes - are tested in a wide range of concentrations. The optimum concentrations of these deflocculants, which result in minimum apparent viscosity of suspension, are found. Sedimentation stability of deflocculated suspensions is monitored. Inorganic electrolytes are found to be more effective in viscosity reduction. On the other hand, low-molecular-weight polyelectrolytes produce more stable final suspensions.